A new species of dwarf goby of Trimma (Teleostei: Gobiidae) from Taiping Island, South China Sea - Chang, Chih-Wei; Shen, Kang-Ning; Chen, I-Shiung (Zootaxa, 2025)
A rare coral-reef dwarf goby was collected recently from Taiping Island, South China Sea. The new species, Trimma taipinensis, can be well distinguished from other congeners by the following unique combination of features: (1) fin ray counts D2 I/7, A I/7, P 17, V with complete sucking disc; (2) squamation including LR 29–30, TR 9, SDP 9, PreD 7, opercle with large scales; (3) no any canal pores; and (4) distinctive colouration: body pale white background with lower half entirely orange yellow. Three cross bands in front of first dorsal fin origin; seven major vertical crossing bands after origin of first dorsal fin. Head with one red bar crossing snout to both jaws, another one vertical red stripe below eye, a vertical red band crossing the edge of preopercle. Nape with two orange red bands. Pectoral fin pinkish to orange, its basal region with two rounded snow white marks. Caudal fin entirely pinkish orange. No any black blotch on caudal fin base. A brief comparison with related species will also be provided.